Examining The Link Among Customer Relationship Management, Market Orientation and Marketing Performance on Small and Medium Enterprises - Wahyuni, Evy; Ardani, Wayan; Widani, Ni Made (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
The aim of this research was to determine the effect customer relationship management on market orientation and marketing performance of SMEs in Denpasar. The research was conducted at PT. GIEB Indonesia in Denpasar. Respondents in this research were customers of PT. GIEB Indonesia that was not definitive estimate of the population size. The sample size for this research was 100 respondents, calculated based on Rao Purba formula. Data collection for this research was carried out using questionnaires, interviews and observations. The collected questionnaire data was analyzed using descriptive analysis and Partial Least Square (PLS). The research revealed that Customer relationship management had a positive and significant effect on market orientation and marketing performance at PT. GIEB. It was also found that market orientation had a positive and significant effect on marketing performance at PT. GIEB Indonesia. The result of this research can be as reference for PT. GIEB Indonesia and other SMEs that customer relationship management and market orientation have important roles in improving marketing performance.